A finite element model of abdominal human tissue for improving the accuracy in insulin absorption assessment: A feasibility study. (December 2021) - Arpaia, Pasquale; Cuneo, Davide; Grassini, Sabrina; Mancino, Francesca; Minucci, Simone; Moccaldi, Nicola; Sannino, Isabella
Abstract: A Finite Element Model of the human abdomen biomechanics for patients undergoing diabetes therapies was developed. In particular, FEM was used to improve a previous insulin absorption measurement method based on bioimpedance spectroscopy (BIS). As a matter of facts, the noise introduced during the insulin injection phase significantly affects the BIS measurements. The noise, due to the pressure exerted on the abdomen tissue, arises sensibility issues on the signal correlated to the drug presence under the skin. In this study, the abdomen is modeled with three layers (skin, fat and muscle). A feasibility study about the decoupling of the mechanical deformation and the electrical dynamics is presented in order to model the effect of mechanical uncertainty sources (e.g., pressure exerted during the injection phase and/or breathing) on the impedance measurements. The proposed simplified model is realised by referring to the average values of skin, fat and muscle thickness, along with mechanical abdomen parameters al-ready presented and validated in scientific literature. The obtained results confirm the possibility to decouple me-chanical and electrical analyses when the excitation voltage is characterized by a frequency higher than 1 kHz. The results will be used to improve the accuracy of an exhaustive approach, already developed by the authors, for real-time insulin absorption measurement.